CoQ10-loaded liposomes combined with UTMD prevented early nephropathy of diabetic rats - Chen, Pian-Pian; Xu, He-Lin; Ting-Yue; ZhuGe, De-Li; Jin, Bing-Hui; Zhu, Qun-Yan; Shen, Bi-Xin; Wang, Li-Fen; Lu, Cui-Tao; Zhao, Ying-Zheng; Li, Xiao-Kun (Oncotarget, 2018)
Nephropathy is one of the most severe complications of diabetic patients. The therapeutic strategies for diabetic patients should not only focus on the control of blood glucose but also pay attention to the occurrence of diabetic nephropathy (DN). Coenzyme Q10 (CoQ10) has great therapeutic potential for DN. However, the clinical application of CoQ10 has been limited because of its low water-solubility and non-specific distribution. Liposomes were supposed to be an effective way for delivering CoQ10 to kidney. CoQ10 was effectively encapsulated into the liposome (CoQ10-LIP) with a high entrapment efficiency of 86.15 %. The CoQ10-LIP exhibited a small hydrodynamic diameter (180 ± 2.1 nm) and negative zeta potential (-18.20 mV). Moreover, CoQ10-LIP was combined with ultrasound-mediated microbubble destruction (UTMD) to enhance specific distribution of CoQ10 in kidney. In early stage of diabetic mellitus (DM), rats were administrated with CoQ10-LIP followed by UTMD (CoQ10-LIP+UTMD) to prevent occurrence of DN. Results revealed that CoQ10-LIP+UTMD effectively prevented the renal morphology and function of diabetics rats from damage. The protective mechanism of CoQ10-LIP was highly associated with protecting podocyte, promoting vascular repair and inhibiting cell apoptosis. Conclusively, CoQ10-LIP in combination with UTMD might be a potential strategy to prevent occurrence of DN.